IMPLEMENTASI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) - Susanti Hartono, Rina; Ariya Tama, Tata (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2024)
To reduce problems regarding land in the Bekasi Regency area which is still not certified and provide legal certainty to landowners. The government issued a program to facilitate the community in obtaining land rights certificates, namely the Complete Systematic Land Registration (PTSL) program. This research uses descriptive research methods with a qualitative approach. Data collection techniques are carried out using interviews, observations, and documentation related to implementing the Complete Systematic Land Registration (PTSL) program. The data obtained are then analyzed qualitatively using the theory proposed by Donald S. Van Meter and Van Horn which includes policy standards and objectives, resources, communication between organizations, characteristics of implementing agents, social and economic conditions, and dispositions of implementors. The results showed that implementing the Complete Systematic Land Registration (PTSL) program at the Bekasi Regency Land Office in general has been going well. However, implementing the Complete Systematic Land Registration (PTSL) has not been optimal due to several inhibiting factors, namely minimal facilities and infrastructure and lack of public awareness in completing administrative requirements, thus slowing down the implementation of the PTSL program in Bekasi Regency.